Artificial intelligence (AI) in healthcare: Opportunities, ethical and legal challenges, and mitigation strategies - Roy, Bedanta (Journal of Biomedical Sciences, 2024)
Integrating artificial intelligence (AI) into healthcare is a revolutionary step and an excellent opportunity to improve patient outcomes, operational efficiencies, and diagnostic precision. However, ethical, legal, and social challenges persist, which must be appropriately addressed to ensure equitable, safe, and trustworthy healthcare systems.